Catalysts for fuel cell: Production and characterization - Franco, Egberto Gomes; Linardi, Marcelo (Revista Ciências Exatas, 2008)
Fuel cells technology is one of the most promising technologies for this century to deal with energy sustainability. In order to improve fuel cells performances the search for new electrocatalysts has a great importance in this technology. The colloidal method was chosen to produce the catalysts because a good nanocrystal distribution can be obtained. This method consists in the production of a stable colloid that will be anchored in the support (carbon black Vulcan XC 72 R). The catalysts were investigated by the following techniques: energy dispersive analysis (EDX), X-rays powder diffraction (XRD), X-rays photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM) and polarization curves (Exi). The binary and ternary catalysts systems synthesized in this work were tested for the oxidation of hydrogen, H2/CO mixtures (150 ppm of CO), methanol and ethanol. The catalyst systems produced by the colloidal method presents a highly-dispersed nanocrystals structure with an average size of 2.0 to 3.1 nm. The electrocatalytic activity of the synthesized Pt-Ru-Mo catalysts for reformate and methanol oxidation was evidenced by polarization curves showing a very promising system to be optimized. PtRuDy behavior is compared to state of the art catalysts for direct ethanol fuel cells (DEFC) and should be tested in long term experiments in direct ethanol fuel cells. Only both structural and electrochemical characterization together will result in a detailed understanding of the effect of the structure on the eletrocatalytic activity of catalysts in real fuel cell systems. This work is part of a systematic research of the fuel cell group of IPEN/CNEN-SP and further investigations in the performance of these catalysts will be done. The PtRuMo system could be used for technical applications.